Effects of Traffic Calming Measures on Mobility, Road Safety and Pavement Conditions on Abuakwa-Bibiani Highway - Damsere-Derry, James; Lumor, Richard; Bawa, Shaibu; Tikoli, David (Frontiers in Sustainable Cities, 2020)
Traffic calming measures (TCMs) have been widely adopted as the major speed control devices in Ghana. While initial evaluations have underscored their effectiveness, little research has been conducted to assess their characteristics relative to design guidelines and the negative externalities associated with their misapplications. The objectives of this research were to; i) establish the characteristics of TCMs, and their implications on mobility; ii) to establish essential speed parameters in communities where TCMs are deployed iii) to establish pavement conditions abutting traffic calming measures and; iv) to analyse the accident typology on the Abuakwa-Bibiani road. Method: Firstly, a radar gun and android speed measuring device were used to unobtrusively measure vehicles’ spot speeds and profiles respectively at different locations relative to the TCMs. Also, visual inspections were carried out to assess the pavement conditions surrounding the TCMs while a geodetic laser levelling instrument and a surveying staff were used to obtain the crown heights of the TCMs. Further, the accident typology on the candidate road were analysed to establish how the TCMs are affecting road crashes. Results: Vehicle speeds were generally lower than the posted speed limits in settlements which have TCMs. Nevertheless, the proportion of accident casualties being pedestrians despite lower speeds in settlements remains unacceptably high. Further, the collision typology on this highway were predominantly loss control and rear-end accidents suggesting that the TCMs are playing insidious roles in some of the crash types on this road. Pavement distresses such as depressions, cracks, rutting, ravelling, potholes and deposit of debris were common in the vicinity of the TCMs. Conclusion: Our findings suggest that awareness creation among communities along the highway may be amenable to improving pedestrians’ safety than relying on only engineering countermeasures. The predominant collision types; loss control and rear-end implies that the TCMs are inadvertently contributing to some accident types. For a long term and sustainable speed control, bypassing settlements, use of active dynamic speed bumps (smart or intelligent speed bumps); and a deterrence-based electronic enforcement such as the Automatic Number Plate Recognition System which uses the demerit points offer better alternatives on the highways.